Flawed advice and the management trap - Argyris, Chris
Flawed Advice and the Management Trap: How Managers Can Know When They're Getting Good Advice and When They're Not is the first book to show how and why so much of today's business advice is flawed, and how managers and executives can better evaluate advice given to their firm